Echocardiographic diagnosis of total or left congenital pericardial absence with positional change. Issue 15 (9th March 2017) - Kim, Min Jeong; Kim, Hyung-Kwan; Jung, Ji-Hyun; Yoon, Yeonyee E; Kim, Hack-Lyoung; Park, Jun-Bin; Lee, Seung-Pyo; Kim, Yong-Jin; Cho, Goo-Young; Sohn, Dae-Won; Oh, Jae K
Abstract : Objectives: Congenital absence of the pericardium (CAP) is often confused with other conditions presenting with right ventricular dilatation and usually warrants CT or cardiac MR (CMR) to confirm. It would be desirable to have more specific echocardiographic criteria to provide a conclusive diagnosis. Methods: 11 patients who were diagnosed with CAP (four patients with total CAP) based on CT/CMR were consecutively enrolled. Thirteen patients with atrial septal defect (ASD) and 16 normal subjects served as controls. To investigate spatial changes of heart in the thoracic cavity in CAP, following echocardiographic measurements were made in the left and right decubitus positions: the angle between the ultrasound beam and the left ventricular posterior wall (Angle-PW ) in end-diastole at the parasternal long axis, and the distance between the chest wall and the most distal part of the left ventricular posterior wall (Distance-PW ) at the parasternal mid-ventricular short axis. Results: Angle-PW in patients with CAP were significantly greater than in those with ASD (100.1±12.5° vs 74.5±8.6°, p<0.017) or in normal subjects (100.1±12.5° vs 69.9±7.6°, p<0.017) at the left decubitus, and the difference in Angle-PW according to posture (left vs right) was significantly greater in CAP compared with the other groups (CAP 20.7±12.7°, ASD 0.31±1.80°, normal 0.31±1.40°, all p<0.017). The differences in Distance-PW according to patient position (CAP 2.43±0.77°, ASD 0.42±0.45°, normal 0.26±0.55°) or cardiac cycle in each position (left: CAP 1.60±0.76°, ASD 0.41±0.27°, normal 0.17±0.12°; right: CAP 0.70±0.32°, ASD 0.22±0.19°, normal 0.22±0.13°) were significantly higher in the CAP group than in the other groups (all p<0.017). Conclusions: Patients with CAP have dynamic alteration in cardiac position depending on posture, which is not observed in ASD or in normal controls. Hence, total or left-sided CAP can be reliably diagnosed with positional changes during routine echocardiography.